Optimasi Komposisi Bahan Makanan Atlet Olahraga Menembak dengan Menggunakan Metode Evolution Strategies (ES) - Nuraini Anitasari; Dian Eka Ratnawati; Titis Sari Kusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The main energy source in humans to be able to grow and develop to be more optimal obtained from the food consumed. Based on differences in each food composition that has been consumed consisting of carbohydrate content, fat content, protein content, energy and so forth then it is needed an optimal diet for each individual. The role of an optimal diet is very important, especially for athletes in order to perform. Shooting sports is one sports that requires endurance aspect for athletes. In addition to regular exercise, so athletes should also be able to manage the portion and food consumption in order to success. In this research, Evolution Strategies algorithm is implemented to optimize the composition of food for shooting athletes with total food ingredients that are used 125 foods. Then reproduction process in this research using mutation method and selection process using elitism selection. Based on the results of the algorithm parameter test, the best population size was obtained by 30 individuals, the size of best offspring as 7Î¼, the best generation number of 60 generations and with the best fitness average 0,004904. Meanwhile, based on the trial of case studies conducted 4 times, it is known that the system is able to produce the result of food composition with minimal prices and it is also known that according to the indicator of nutritionist in assessing food consumption, carbohydrate and fat is categorized as sufficient and protein is categorized as good with an average carbohydrate is 90,1%, fat is 98,7% and protein is 105,4%.